Evaluation of the Transboundary Aquifer Agreements from the WEFE Nexus perspective - Ramos, Silmara Juliana de Oliveira; Matos, Lucas dos Santos; Wantzen, Karl Matthias (Revista de Administração da UFSM, 2025)
Purpose: Recognizing the holistic perspective that encompasses the interconnections between water, energy, food, and ecosystems, it becomes important to highlight the discussion about aquifer studies integrating the concepts of WEFE Nexus. Considering that the management of transboundary aquifers relies on agreements signed between countries, it is relevant to investigate this topic by including it in the framework of the WEFE Nexus. In this regard, the objective of this study is to understand how the water-energy-food-ecosystem Nexus context is addressed in transboundary aquifer agreements. Methodology: The study adopted a qualitative approach, developing a core concept for the WEFE Nexus, composed of five analytical perspectives. This framework was developed through a systematic review of the literature based on SCOPUS and Web of Science databases. Transboundary aquifer agreements were subsequently analyzed according to each analytical perspective, facilitating the identification of key issues, gaps, and opportunities in alignment with the WEFE Nexus context. Findings: We noted that none of the agreements fulfilled all the created perspectives. None of the agreements included data illustrating synergy among water, energy, food, and ecosystem resources, nor did they provide guidelines concerning the trade-offs among these resources. There are opportunities to enhance agreements and advance the objectives of the WEFE Nexus through improvements in Monitoring, Stakeholders, and Governance perspectives. Originality/value: The WEFE Nexus approach seeks to achieve a better balance in the use of natural resources essential for human well-being. However, technical improvements are necessary within the agreements, taking into account the individual characteristics and requirements of each aquifer within the context of the WEFE Nexus. Finally, the primary contributions of the research are associated with providing a fresh approach and perspective to the discourse surrounding the management and governance of transboundary aquifers. In this regard, it extends beyond the scope of water alone and encompasses the other interconnected resources within this context.